Rootstock Growth and Green Budding Success of Rubber Plant in Different Sizes of Polybag and Growing Media - Rusli Rusli; Nana Heryana; Saefudin Saefudin (Pusat Penelitian dan Pengembangan Perkebunan, 2014)
Volume and type of growing media is important to support the growth of rubber seedling (Hevea brasiliensis) for rootstocks. The objective of this study was to determine the growth of rootstock and green budding success of rubber plants in different size of polybag and growing media. The research was carried out since January to December 2013 at the Pakuwon experimental garden, Parungkuda District, Sukabumi Regency, West Java. The study used a randomized block design (RBD) in factorial with two factors and three replications. The first factor is the sizes of polybag: (1) 30 ´ 20 cm, (2) 35 ´ 20 cm, and (3) 40 ´ 20 cm. Meanwhile, the second factor is the growing medium that consists of the mixture of soil and cow manure with 4 proportions: (1) 1 : 0, (2) 3 : 1, (3) 2 : 1, and (4) 1 : 1. Observations were made on the growth of pre-budding rootstock including seedling height, seedling diameter, number of leaves, and the success percentage of green budding. The results showed that the size of polybag has positive effect on the growth of the rubber seedling as rootstock at 6 months old after planting. Moreover, the use of large sizes of polybag (30 x 20–40 x 20 cm) was good for the growth of rootstocks that would be used for green budding. In addition, growing media that consisted of soil and cow manure at a comparison of 1 : 1 gave the highest effect on the growth of rootstock as well as the highest percentage of green budding success. However, there is no interaction between the size of polybag and growing media to the growth of rootstock and green budding success.